Allelic and haplotypic polymorphisms and paternal genetic analysis of Chinese Shaanxi Han population utilizing a multiplex Y-STR set - Hui Xu; Ming Zhao; Shuyan Mei; Yunying Zhang; Meiming Cai; Fanzhang Lei; Bofeng Zhu (Annals of Human Biology, 2022)
Background The analysis of Y chromosomal genetic markers is of great significance in human genetic fields related to male individuals. The Han nationality is the most populous ethnic group. It is critical to investigate the Y-chromosome short tandem repeat (Y-STR) genetic informativeness of Han nationalities in different Chinese regions in order to gain a comprehensive understanding of their paternal genetic relationships and origin. Aim To assess the allelic and haplotypic polymorphisms of the novel AGCU Y SUPP STR amplification system containing seven Y-STRs in the maximal dataset of the Y-STR Haplotype Reference Database (YHRD) and 17 newly included Y-STRs, and explore the genetic relationships among the Shaanxi Han population and 12 reference populations from China. Subjects and methods A total sample of 220 Han male subjects were obtained from the Shaanxi Province, China, and genotyped by the novel AGCU Y SUPP STR amplification system. Multiplex population genetic analyses derived from the same 16 Y-STR loci were carried out among the Shaanxi Han population and 12 reference populations from China. Results The gene diversities (GD) ranged from the maximum value of 0.9609 (DYS385a,b) to the minimum value of 0.5441 (DYS531). Besides, 217 distinct haplotypes were detected wholly in 220 individuals, of which 214 (98.62%) were exclusive. The entire haplotype diversity (HD) and discrimination capacity (DC) were 0.9999 and 0.9864, respectively, while the haplotype match probability (HMP) was 0.0045. Among the reference populations, the obtained results of population genetic analyses revealed that the Shaanxi Han population had the largest genetic distance with the Guangxi Yao group, but the smallest genetic distance with the Hunan Tujia group. Conclusions These Y-STR loci in the AGCU Y SUPP STR amplification system were of high genetic polymorphisms and the amplification system could be used as a prospective complementary tool for forensic application and paternal genetics in the Shaanxi Han population.